ANALISIS KINERJA CONDENSER SHELL AND TUBE UNIT 2 DI PT. PLN (PERSERO) SEKTOR ASAM-ASAM KALIMANTAN SELATAN - Hairudin, Hairudin; Mursadin, Aqli (Universitas Lambung Mangkurat, 2021)
Theecondenser is a type of heat exchanger that functions to condense fluid. On steam powermsystems. Thevmain function ofmthe condenser is to convert steam into liquid. The purpose of this study is to determine the value and influence of heat balance, heat transfer coefficient, pressure drop and condenser efficiency.Thewresults offthissstudy indicate that in 2018 thee average heat balance (Q) was obtained at 356,017,533.46 Kj / hour while in 2019 the results of the average heat balance (Q) were 640,293,647,066 Kj / hour, fouling factor was not affect the balance sheet. The average gross heat transfer coefficient (UD) in 2018 amounted to 204,274.25 Kj / hour.m2. C and the average net heat transfer coefficient (UC) was 206,378 Kj / hr.m2. ° C whereas in 2019 the average heat transfer coefficient is obtained by the average gross heat transfer coefficient (UD) of 366,544.07 Kj / jam.m2. ° C and the Clean heat transfer coefficient (UC) is 448,554 Kj / h.m2. ° C.Fouling factor is very influential onnthe heatwtransfer coefficient because the greater the fouling in the tube will result in the inhibition of theeheat transfer rate in the tube, so that the heat transfer coefficient decreases. The pressure drop in 2018 is still within the permissible limits, with an average of 504.28 bars and 2019 of 513.03 bars. The effectiveness of the condenser in 2018 is an average of 23.330 after maintenance has been obtained, the average effectiveness of the condenser in 2019 is 40.743